Meanings and Messages of The Song Lyrics in Iwan Fals' "Wakil Rakyat" Album - Amin Diwan Waruwu, Tengku; Wayan Budiarta, I; Nyoman Muliana, I (KnE Social Sciences, 2022)
The purpose of this study was to investigate the Meanings and Messages of The Song Lyrics. This study used qualitative methods with a descriptive approach. The researcher employed himself to collect the data by reading whole lyrics of the songs contained in the album and listening to them, marking the sentences that matter. The researcher used the songs of Iwan Fals in his album entitled Wakil Rakyat. After analyzing the lyric of the song which are composed by Iwan Fals, the researcher made the conclusion. The researcher concluded that each song in this album contains different meanings and messages even though some songs have the similarity. The following were the meaning and message contained in each song; conceptual meaning, connotative meaning, collocative meaning, stylistic meaning, affective meaning, and thematic meaning. While the song’s message is Iwan Fals giving advice, criticism, and appeals to teachers, students, the Indonesian legislative assembly, children, parents, farmers, employees, and a variety of other professions. There are numerous terms with various meanings and messages. The conclusion is that a composer or songwriter manipulates words or languages to create an appeal to the lyrics to express his experience. Song lovers, teachers, students, and everyone else who enjoys listening to music should be able to understand the song’s meaning and message thanks to this research. Keywords: meanings, messages, song lyrics of Iwan Fals, “Wakil Rakyat